2015
DOI: 10.1002/cbf.3128
|View full text |Cite
|
Sign up to set email alerts
|

Role of exercise intensity on GLUT4 content, aerobic fitness and fasting plasma glucose in type 2 diabetic mice

Abstract: Type 2 diabetes mellitus (T2D) results in several metabolic and cardiovascular dysfunctions, clinically characterized by hyperglycaemia due to lower glucose uptake and oxidation. Physical exercise is an effective intervention for glycaemic control. However, the effects of exercising at different intensities have not yet been addressed. The present study analysed the effects of 8 weeks of training performed at different exercise intensities on type 4 glucose transporters (GLUT4) content and glycaemic control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Although the analgesic effects of EA are well documented, its mechanisms are poorly understood. Present studies have indicated that EA may improve insulin resistance [64,65] by enhancing insulin sensitivity in rats [66]. Previously, we have shown that both 2 Hz and 100 Hz EA stimulation relieve DNP, but 2 Hz EA has a stronger analgesic effect [67].…”
Section: Discussionmentioning
confidence: 83%
“…Although the analgesic effects of EA are well documented, its mechanisms are poorly understood. Present studies have indicated that EA may improve insulin resistance [64,65] by enhancing insulin sensitivity in rats [66]. Previously, we have shown that both 2 Hz and 100 Hz EA stimulation relieve DNP, but 2 Hz EA has a stronger analgesic effect [67].…”
Section: Discussionmentioning
confidence: 83%
“…A recent study in healthy and obese mice has evaluated the impact of exercise intensity on the physiological adaptations to exercise training program 60 . This study showed that higher exercise intensity allowed better improvement of skeletal muscle Glut4 content and glycaemic control in obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…A positive outcome on brain maturity as well as metabolism depends on frequency, duration, and intensity of the exercise (Ploughman et al, 2007; Speck et al, 2014). Swimming is rather forced work out for rodents and studied as aerobic exercise to challenge the metabolism and immune system (Wasinski et al, 2013; Cunha et al, 2015). Only few studies address the effect of swimming exercise on the brain revealing a neuroprotective role in Parkinson's disease, and increased neurotrophin levels (Goes et al, 2014; Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%